FIQIH ANTI-KORUPSI MAZHAB NEGARA: Memadu Hukum Islam dan Hukum Nasional - Maghfur Ahmad (Jurnal Hukum Islam, 2014)
Corruption is an ironic behavior of country executors. This white collars crime has been run structurally, sistematically, and massively. The effect is not only make the country financial be bad, but also sacrifice the the humanity aspect, the natural source, and the next generation prestige. The experts in classic fiqh (fuqaha) had discussed corruption discourse, eventhough in different contexts and frames. This article tried to investigate the discourse, the removing, and the sanction of corruption behavior in Islamic law perspective in the framework of Indonesian constitution regulation. Based on the deep investigation, fiqh reports the study constructions of sariqah, ghulul, risywah, ghasab, and so on, substantially, have relevance with the corruption investigation in Indonesia. That is why the fiqh contribution in removing corruption in Indonesia becomes real, especially related with the concepts, sanctions, prevention efforts, and the tackling of corruption and its effects in Indonesia.